2005
DOI: 10.1128/jcm.43.10.5048-5054.2005
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Molecular Analysis of Extended-Spectrum β-Lactamase-Producing Enterobacteria in the Community Setting

Abstract: During a previous survey, five extended-spectrum ␤-lactamase (ESBL)-producing enterobacteria (ESBLE) (two Enterobacter aerogenes isolates expressing TEM-24b, two Escherichia coli isolates expressing TEM-21 or TEM-24b, and one Klebsiella pneumoniae isolate expressing SHV-4/TEM-15) responsible for urinary tract infections (UTIs) were found among 1,584 strains collected from community patients. The aim of the present study was to elucidate the route of emergence of these typically nosocomial organisms in the comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
0
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 32 publications
(56 reference statements)
2
26
0
4
Order By: Relevance
“…This fact further supports the horizontal migration of P. aeruginosa from the hospital environment to the community setting. Consistent with our observations, previous studies have also demonstrated that community-onset infections due to ESBL-producing gram-negative bacteria often result from nosocomial acquisition of the strains or their genetic elements (1). Moreover, genitourinary pathology, a finding common in our patients, has been recognized as an independent risk factor for community-onset infections caused by ESBL-producing organisms (2).…”
Section: Discussionsupporting
confidence: 78%
“…This fact further supports the horizontal migration of P. aeruginosa from the hospital environment to the community setting. Consistent with our observations, previous studies have also demonstrated that community-onset infections due to ESBL-producing gram-negative bacteria often result from nosocomial acquisition of the strains or their genetic elements (1). Moreover, genitourinary pathology, a finding common in our patients, has been recognized as an independent risk factor for community-onset infections caused by ESBL-producing organisms (2).…”
Section: Discussionsupporting
confidence: 78%
“…Nursing homes, in turn, may serve as reservoirs from which colonized and infected patients transfer to the community or back to the hospitals [8,32]. Prior to the rise of CTX-M, such a model seemed to have corresponded with the available data [33]. Even after the noted spread of bacteria producing CTX-M into the community, recent hospitalization, along with age and exposure to cephalosporins and/or quinolones, have consistently been identified as risk factors for infection with these organisms [8,34,35].…”
Section: The Emerging Threat Of Ctx-m Beta-lactamases In the Communitymentioning
confidence: 99%
“…Porast rezistencije uropatogena bio je mnogo veći problem bolničkih sredina. Međutim, studijama sprovedenim u poslednjih deset godina, pokazan je porast rezistentnih sojeva i u opštoj populaciji (20)(21)(22)(23)(24)(25). iz ovog razloga, treba biti obazriv prilikom empirijskog propisivanja terapije, naročito ako se radi o starijim osobama, osobama s hroničnim oboljenjima, ili osobama s malformacijama urinarnog trakta.…”
Section: Tabela 5 Izolati Snižene Osetljivosti Na Cefalosporine IIIunclassified